One false note [compact disc, unabridged] - Korman, Gordon (39 clues, 2008)
"The race is on to find 39 clues that safeguard a great power, and fourteen-year old Amy Cahill and her younger brother, Dan, are shocked to find themselves in the lead. The search seems to be taking them to Vienna, and they hold a coded piece of Mozart's sheet music that's key to finding the next clue. But tailed by a pack of power-hungry relatives, Amy and Dan can't see if they are sailing toward victory or straight into a deadly trap"--Container.